Reform And Inequality During The Transition : An Analysis Using Panel Household Survey Data, 1990-2005 - Milanović, Branko, 1953- 1953- (The World Bank, 2008)
Using for the first time household survey data from 26 post-Communist countries, covering the period 1990-2005, this paper examines correlates of unprecedented increases in inequality registered by most of the economies. The analysis shows, after controlling for country fixed effects and type of survey used, that economic reform is strongly negatively associated with the income share of the bottom decile, and positively with the income shares of the top two deciles. However, breaking economic reform into its component parts, the picture is more nuanced. Large-scale privatization and infrastructure reform (mostly consisting of privatization and higher fees) are responsible for the pro-inequality effect; small-scale privatization tends to raise the income shares of the bottom deciles. Acceleration in growth is also pro-rich. But democratization is strongly pro-poor, as is lower inflation. Somewhat surprisingly, the analysis finds no evidence that greater government spending as share of gross domestic income reduces inequality